Effects of inter-firm technology transfer characteristics on degree of inter-firm technology transfer in International Joint Ventures - Abdul Wahab, Sazali; Abdullah, Haslinda; Uli, Jegak; Che Rose, Raduan (European Journals, Inc., 2009)
The inter-firm technology transfers (TT) in collaborative joint ventures (JVs) often involve tradeoffs between the willingness of technology supplier to transfer a considerable amount of technologies to technology recipient and degree of protection of the proprietary technology, knowledge and competencies as the source of the supplier’s competitive advantage. Thus, technology transfers through JVs, although have been acknowledged in many studies as the most efficient mechanism in internalizing the partner’s technology,knowledge and skill, have frequently involved various facilitators, actors and complicated relationship between partners that have direct impact on the degree or amount of technology transferred in JVs. Building on the integrated knowledge-based view and organizational learning perspectives, and previous TT models, this study proposes a holistic TT model in providing explanations on the relative and simultaneous effects of technology transfer characteristics (TTCHARS) on degree of technology transfer (TTDEG). Subsequently, the holistic TT model also conceptualizes the effect of TTDEG on local firms’ performance dimensions namely corporate and human resource performance, and the moderating effects of MNCs’ firm size, age of JV, MNCs’ country of origin, and types of industries in the TTCHARS-TTDEG relationship.